A risk analysis model for fire disasters in commericial complexes in Nigeria (2010)
The frequent occurrence of fire accidents in commercial complexes has become a serious problem in Nigeria. The development of a quantitative tool for evaluating the proneness of a commercial complex to so called 'market fires' is the focus of this study. A rigorous review of the literature was carried to identify and characterize some existing risk analysis models applicable to the problem. Some past fire disasters were analyzed. Using the insight gained from the above, a mathematical model incorporating the modularization features of the Optimum Risk Analysis (ORA) model was developed. Graphical User Interface (GUI) based computer software of the model was developed and used to analyze some existing complexes in Lagos and Ibadan cities of Nigeria and results compared with past record of fire accidents. The application of the model and the associated software indicates its suitability in predicting fire accidents. Insurance companies and other stakeholders will find it useful.